Association between atrial septal aneurysm and arrhythmias. (3rd May 2020) - Yetkin, Ertan; Ileri, Mehmet; Korkmaz, Ahmet; Ozturk, Selcuk
Abstract: Objective. This study aimed to assess the association of atrial septal aneurysm (ASA) with cardiac arrhythmias by comparing patients with ASA with a control group with non-ASA, matched for age and gender. Methods. 641 patients with ASA who fulfilled the inclusion criteria were enrolled into the study. The control group consisted of 641 patients without ASA. Patients underwent physical, electrocardiographic and transthoracic echocardiographic examinations. Additional examinations such as transesophageal echocardiography, 24-h rhythm Holter monitoring, and electrophysiological study were performed when clinically needed. Results. There were no differences between the groups in respect to baseline demographic, clinical parameters and echocardiographic parameters except ischemic stroke and smoking status. Percentages of patients suffering from atrial premature complex (APC), ventricular premature complex (VPC), supraventricular tachycardia (SVT) and paroxysmal atrial fibrillation (AF) were higher in ASA patients compared to non-ASA patients. In addition, these parameters were independently associated with the presence of ASA in logistic regression analysis. Conclusions. Certain types of arrhythmias such as APC, VPC, SVT and paroxysmal AF have been shown to be independently associated with the presence of ASA.